The Reagan diaries - Reagan, Ronald; Brinkley, Douglas (New York : Harper Perennial, 2007)
During his two terms as the fortieth president of the United States, Ronald Reagan kept a daily diary in which he recorded, by hand, his innermost thoughts and observations on the extraordinary, the historic, and the routine day-to-day occurrences of his presidency. Whether he was in his White House residence study or aboard Air Force One, from his first inauguration to the end of the Cold War, each night Reagan wrote about the events of his day. Now, nearly two decades after he left office, this record--the only daily presidential diary in American history--is available for the first time. Brought together in one volume and edited by historian Douglas Brinkley, The Reagan Diaries provide insight into one of this nation's most important presidencies and sheds new light on the character of a true American leader.--From publisher description.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Reagan, Ronald -- Diaries; Presidents -- United States -- Biography; Presidents -- United States -- Diaries; United States -- Politics and government -- 1981-1989.